Development of multi-targetable chalcone derivatives bearing N-aryl piperazine moiety for the treatment of Alzheimer's disease - Bajad N.G.; Singh R.B.; Gajendra T.A.; Gutti G.; Kumar A.; Krishnamurthy S.; Singh S.K. (My University, 2025)
The multi-target directed ligand (MTDL) discovery has been gaining immense attention in the development of therapeutics for Alzheimer's disease (AD). The strategy has been evolved as an auspicious approach suitable to combat the heterogeneity and the multifactorial nature of AD. Therefore, multi-targetable chalcone derivatives bearing N-aryl piperazine moiety were designed, synthesized, and evaluated for the treatment of AD. All the synthesized compounds were screened for the in vitro activity against acetylcholinesterase (AChE), butylcholinesterase (BuChE), β-secretase-1 (BACE-1), and inhibition of amyloid β (Aβ) aggregation. Amongst all the tested derivatives, compound 41 bearing unsubstituted benzylpiperazine fragment and para-bromo substitution at the chalcone scaffold exhibited balanced inhibitory profile against the selected targets. Compound 41 elicited favourable permeation across the blood–brain barrier in the PAMPA assay. The molecular docking and dynamics simulation studies revealed the binding mode analysis and protein–ligand stability of the compound with AChE and BACE-1. Furthermore, it ameliorated cognitive dysfunctions and signified memory improvement in the in-vivo behavioural studies (scopolamine-induced amnesia model). The ex vivo biochemical analysis of mice brain homogenates established the reduced AChE and increased ACh levels. The antioxidant activity of compound 41 was accessed with the determination of catalase (CAT) and malondialdehyde (MDA) levels. The findings suggested that compound 41, containing a privileged chalcone scaffold, can act as a lead molecule for developing AD therapeutics. © 2023 Elsevier Inc.